FENOMENA FEAR OF MISSING OUT PADA GENERASI MILLENIAL DALAM JEJARING SOSIAL MEDIA INSTAGRAM - Ningyastuti, Wiji Rahayu (Jurnal Visi Komunikasi, 2022)
Millennials continue to communicate with their friends on social media, and even follow social media trends to show that they are up-to-date and live a happy life. This phenomenon of Fear of Missing Out is examined by the authors in this study. This research aims to find out how FoMO occurs in millennials who use Instagram. This study uses descriptive research with a qualitative approach. Use the phenomenology of Alfred Schutz to illustrate what motivates the millennial generation to use Instagram, the causes of FoMO, the content that causes FoMO, indications of FoMO, as well as the characteristics of FoMO. The results obtained are the millennials who use Instagram excessively can cause FoMO, millennials who experience FoMO in Instagram has several indications and also certain characteristics. Such as fear, anxiety, and worry.